OVERVIEW OF POWER PLANTS FOR UNMANNED AIRCRAFT SYSTEMS - Bogunenko, Nikolay; Yastrub, Maxym; Zastola, Julia (Proceedings of National Aviation University (archive), 2015)
This article is devoted to general overview of nowadays existent power plants intended for use in unmanned aircraft systems and types of fuel or sources of energy that can be used in power plants using open source of information.